Synthesis, biophysical properties, and RNase H activity of 6’-difluoro[4.3.0]bicyclo-DNA - Frei, Sibylle; Katolik, Adam K.; Leumann, Christian J. (Beilstein Journal of Organic Chemistry, 2019)
Here we present the synthesis, the biophysical properties, and the RNase H profile of 6’-difluorinated [4.3.0]bicyclo-DNA (6’-diF-bc4,3-DNA). The difluorinated thymidine phosphoramidite building block was synthesized starting from an already known gem-difluorinated tricyclic glycal. This tricyclic siloxydifluorocyclopropane was converted into the [4.3.0]bicyclic nucleoside via cyclopropane ring-opening through the addition of an electrophilic iodine during the nucleosidation step followed by reduction. The gem-difluorinated bicyclic nucleoside was then converted into the corresponding phosphoramidite building block which was incorporated into oligonucleotides. Thermal denaturation experiments of these oligonucleotides hybridized to complementary DNA or RNA disclosed a significant destabilization of both duplex types (ΔTm/mod = −1.6 to −5.5 °C). However, in the DNA/RNA hybrid the amount of destabilization could be reduced by multiple insertions of the modified unit. In addition, CD spectroscopy of the oligonucleotides hybridized to RNA showed a similar structure than the natural DNA/RNA duplex. Furthermore, since the structural investigation on the nucleoside level by X-ray crystallography and ab initio calculations pointed to a furanose conformation in the southern region, a RNase H cleavage assay was conducted. This experiment revealed that the oligonucleotide containing five modified units was able to elicit the RNase H-mediated cleavage of the complementary RNA strand.
Keywords: DNA/RNA affinity; fluorinated cyclopropanes; fluorinated nucleic acids; RNase H activity; sugar modified nucleosides